Tensile behavior of hybrid natural/glass fibers reinforced composites at different temperatures - Wan Yaakob, Wan Noor Azira (2007)
Nowadays, natural fiber reinforced composites are given bright opportunities to replace synthetic fiber reinforced composites especially in automotive sectors. Natural fibers offer considerable high strength, low weight and less abrasive effect. But this fiber is incompatible to polymeric material which leads to interfacial bonding problems. To encounter this problem, hybridization between natural and synthetic fibers are formulated and tested. In this work, coir and glass fibers are blended mechanically with polypropylene granular to homogenize the composite mixture. Both fibers are chemically treated to enhance the bonding with matrix material. It is then extruded into identical dimensions and shape (dog-bone tensile specimen). Several different temperatures are selected ranging from room temperature to I00°C and the specimens are quasi-statically stressed at constant cross-head displacement l.Smm/min. It is found that the interaction between fiber hybridizations and temperatures played an important role in determining the tensile behavior of this composite. Scanning electron microscope (SEM) is used to observe the fracture surfaces of these samples after tensile tests. Different toughening mechanisms are observed such as fiber pull-out and interfacial detachments which are depend on the temperature and fiber volume fraction